3 - Effets de l’aide internationale sur l’agriculture africaine: Le cas du Maroc: by Driss Khrouz - Driss Khrouz (Africa Development, 1992)
In the last three decades , international aid has become a determinant factor th^ Morocco' s choices of economic policy. The sources of aid to the agricultural sector are varied and poorly coordinated as they are administered by numerous institutions with overlapping areas of intervention and competence. Earlier phases of aid to agriculture were aimed at enhancing Morocco's comparative advantage in world agricultural trade within the framework of Morocco's agreements with EEC. Disproportional allocation of resources to the export sector subsidies to rich farmers and the subordination of peasant economy to the export sector resulted in structural disequilibria with very negative socio-economic consequences. In spite of policy shifts and attempts to redress these problems , Morocco was faced with a growing need for food imports and an alarming debt spiral, it became apparent that the State can no longer continue funding the rich and did not have the means nor the will to fund the poor. Funding agencies imposed market mechanisms as the only viable solution.